Online learning in a high-performance sport environment-a mixed-method study - Fyall, G.; Bennett, B.; Cowan, J. (International Sport Coaching Journal, 2023)
This study investigated a high-performance rugby academy program in New Zealand during the COVID-19 lockdown period in 2020. Unsurprisingly, this challenged academy staff who were abruptly charged with conceptualizing and implementing the program in innovative ways including a move to online learning and the adoption of online learning tools. A mixed-method sequential exploratory design was employed to explore the managers, coaches, and learners` experiences. Phase 1 explored three coaches and two academy managers conceptualization and subsequent experiences of the online program. Phase 2 explored 44 academy players` experiences of the online learning program. Our findings reveal that an explicit focus on player well-being and connection online appeared to increase a "sense of community" within and across both cohorts through enhanced communication, participation, and interaction. The challenges encountered included: accessibility, the amount, flow, and direction of information, "app fatigue," and online technologies that were not fit-for-purpose. Our discussion reinforces that purposeful design and constant reflection is requisite to the successful and sustainable implementation of online coaching environments. We conclude with five fundamental lessons learned from COVID-19 that are worthy of consideration in the purposeful design of future online high-performance sporting programmes.